Erwinia chrysanthemi: pectolytic bacterium causing soft rot outbreaks of arracacha in Brazil - Henz, Gilmar Paulo; Reifschneider, Francisco José Becker; Duarte, Valmir (Pesquisa Agropecuaria Brasileira, 2006)
The objetive of this work was to identify the pectolytic bacteria associated with soft rot of arracacha roots in Brazil. From 1998 to 2001, 227 isolates of Erwinia spp. were obtained from arracacha roots and identified by biochemical and physiological tests (pectolytic activity, lecithinase, α-methyl glucoside, phosphatase, erythromycin sensivity, growth at 37°C). Of these isolates, 89.9% were identified as E. chrysanthemi (Ech), 9.7% as E. carotovora subsp. carotovora (Ecc) and 0.5% as E. carotovora subsp. atroseptica. The identity of seventeen out of twenty representative isolates of Ech and Ecc was confirmed by PCR (primers ’149f’, ’L1r’, ’ADE1’, ’ADE2’).